Control of infectious diseases in dairy cattle - Wapenaar, Wendela; Archer, Simon C.; Remnant, J.G.; Murphy, Alan (Burleigh Dodd Science Publishing, 2017)
This chapter describes developments of infectious disease control in the dairy cattle industry, and outlines recent research in this area. A risk analysis approach is presented as a framework for managing infectious disease at global and farm level. Disease hazards, and the release and exposure of these are discussed. The importance of disease detection, the use of diagnostic tests, their appropriate interpretation and surveillance are highlighted. The range of impacts of infectious disease on the dairy industry is described and guidelines to estimate and evaluate risks of infectious diseases are provided. In addition, the challenges around successful implementation and effective communication of risk management on dairy farms are reviewed.